SIMULATION OF SAND PARTICLE FLOW THROUGH SAND SCREEN IN OIL WELL - ZAMANI, MUHAMMAD ALDRIN SYAFRIZAL (IRC, 2020)
Sand production is a process occurs in oil and gas wells during the process of drilling recovery hole. The sandstone being drilled is left unsupported next to the cavity and dislodged sand grains can enter the oil recovery system. Sand production can cause several problems such as clogging up of the well or damage the wall equipment. Thus, the study of sand production is very important for safe and economical oil and gas production. Most of numerical models to predict the behaviour of sand in the well that have been used until now are continuum-based, but this approach cannot easily capture the important properties or features of the sand production problem and it is a difficult task due to the large number of interactions and non-linearities intrinsic to the problem.